Feasibility Pilot Study of a Teaching Kitchen and Self-Care Curriculum in a Workplace Setting. Issue 3 (May 2019) - Eisenberg, David M.; Righter, Allison C.; Matthews, Benjamin; Zhang, Weimin; Willett, Walter C.; Massa, Jennifer
Objective . To examine the feasibility of a prototype Teaching Kitchen (TK) self-care intervention that offers the combination of culinary, nutrition, exercise, and mindfulness instruction with health coaching; and to describe research methods whereby the impact of TK models can be scientifically assessed. Design . Feasibility pilot study. Subjects were recruited, screened, and consented to participate in 14- or 16-week programs. Feasibility was assessed through ease of recruitment and attendance. One-sample t tests and generalized estimating equation models were used to compare differences in groups. Setting . Workplace. Subjects . Two cohorts of 20 employees and their partners. Results . All 40 participants completed the program with high attendance (89%) and response rates on repeated assessments. Multiple changes were observed in biomarkers and self-reported behaviors from baseline to postprogram including significant ( P < .05) decreases from baseline to postprogram in body weight (−2.8 kg), waist circumference (−2.2 in.), systolic and diastolic blood pressure (−7.7 and −6.3 mm Hg, respectively), and total cholesterol (−7.5 mg/dL). While changes in all of the aforementioned biomarkers persisted over the 12-month follow-up (n = 32), only changes in waist circumference and diastolic blood pressure remained statistically different at 12 months. Conclusions . These study findings suggest that a TK curriculum is feasible within a workplace setting and that its impact on relevant behavioral and clinical outcomes can be scientifically assessed.